Acromegaly is associated with increased cancer risk: a survey in Italy. Issue 9 (September 2017) - Terzolo, Massimo; Reimondo, Giuseppe; Berchialla, Paola; Ferrante, Emanuele; Malchiodi, Elena; De Marinis, Laura; Pivonello, Rosario; Grottoli, Silvia; Losa, Marco; Cannavo, Salvatore; Ferone, Diego; Montini, Marcella; et al.
Abstract : It is debated if acromegalic patients have an increased risk to develop malignancies. The aim of the present study was to assess the standardized incidence ratios (SIRs) of different types of cancer in acromegaly on a large series of acromegalic patients managed in the somatostatin analogs era. It was evaluated the incidence of cancer in an Italian nationwide multicenter cohort study of 1512 acromegalic patients, 624 men and 888 women, mean age at diagnosis 45 ± 13 years, followed up for a mean of 10 years (12573 person-years) in respect to the general Italian population. Cancer was diagnosed in 124 patients, 72 women and 52 men. The SIRs for all cancers was significantly increased compared to the general Italian population (expected: 88, SIR 1.41; 95% CI, 1.18–1.68, P  < 0.001). In the whole series, we found a significantly increased incidence of colorectal cancer (SIR 1.67; 95% CI, 1.07–2.58, P  = 0.022), kidney cancer (SIR 2.87; 95% CI, 1.55–5.34, P  < 0.001) and thyroid cancer (SIR 3.99; 95% CI, 2.32–6.87, P  < 0.001). The exclusion of 11 cancers occurring before diagnosis of acromegaly (all in women) did not change remarkably the study outcome. In multivariate analysis, the factors significantly associated with an increased risk of malignancy were age and family history of cancer, with a non-significant trend for the estimated duration of acromegaly before diagnosis. In conclusion, we found evidence that acromegaly in Italy is associated with a moderate increase in cancer risk.